You are on page 1of 4

1

30 2002

:
: (4)

1o
A.

f ' [, ].
G f [, ],

f (t ) dt = G() G() .
12
.1. f(x) = x. f
R
f(x) = x .
8
.2. ,


.
. f [,]
(,], f
[,] .
1
. , 1-1
, .
1

. f x 0
lim f(x) = 0 ,

x x 0

lim f(x) = 0 .
x x 0
1
. f R ,

f (x)dx = xf (x) xf(x)dx .


1
.

lim f(x) > 0 , f(x) > 0 x 0 .


x x 0
1

2
z f() = i z,
. f(3) + f(8) + f(13) + f(18) = 0 .

IN*.
7

. z= Arg(z) = ,



f(13) = + + i + .
2
2

8
. z= 2 Arg(z) =

,
3

0, z f(13).
10

3
f, g R .
fog 1-1.
. g 1-1.

. :
g ( f(x) + x 3 - x ) = g ( f(x) + 2x -1 )
.
18
4
. h, g [, ].
h(x) > g(x) x [, ],

h(x)dx >
g(x)dx .

2
. R f,
:

f ( x) e f ( x ) = x 1,

x R

f(0) = 0 .

f f.

x
< f(x) < x f(x) ,
2

x > 0.
12

)
f, x = 0,
x = 1 xx,
1
1
f (1) .
< E <
2
4
6

1.

2.

3.
4.
5.
6.

( )

(, , ).
.
,
.

.
.

,
.
.
.
: (3)
.
: (1 1/2)
.
K